An Analysis of the Practices of International Commercial Arbitration in Pakistan and the UK - Shahzad Manzoor Khan; Jamil Ahmad Khokhar; Sadia Saeed; Ali Naeem (Indus Journal of Social Sciences, 2025)
The enforcement of international commercial arbitration (ICA) awards is a critical aspect of global trade and investment, ensuring the credibility and effectiveness of arbitration as a dispute resolution mechanism. This paper provides a comparative analysis of the enforcement frameworks in Pakistan and the UK both signatories to the New York Convention (NYC), 1958. While the UK’s Arbitration Act, (AA) 1996 is widely regarded as arbitration-friendly and aligned with international best practices, Pakistan’s arbitration regime, governed by the Arbitration Act, 1940 and the Recognition and Enforcement (Arbitration Agreements and Foreign Arbitral Awards) Act, 2011 (REFA, 2011), has faced challenges in achieving similar efficiency and predictability. The study examines the grounds for refusing enforcement under both jurisdictions, including invalid arbitration agreements, procedural irregularities, excess of authority, and public policy considerations. It highlights the UK’s pro-enforcement stance, characterized by minimal judicial intervention and narrow interpretation of public policy, as seen in cases like Yukos Capital S.A.R.L. v. OJSC Rosneft Oil Company (2012). In contrast, Pakistan’s enforcement framework has historically been hindered by procedural delays, inconsistent judicial interpretations, and a broader application of public policy, as demonstrated in Societe Generale de Surveillance S.A. v. Pakistan (2003). However, recent developments, such as the Broadsheet LLC v. Pakistan (2021) case, indicate progress toward aligning Pakistan’s arbitration practices with international standards. The paper concludes that while the UK serves as a model for effective enforcement, Pakistan’s ongoing reforms under REFA, 2011 offer a promising foundation for improvement. By addressing existing challenges and adopting best practices, Pakistan can enhance its arbitration framework and strengthen its position as a reliable jurisdiction for enforcing international arbitral awards.